Insect diversity in various distances to forest edge in small nature reserve: A case study of Bantarbolang Nature Reserve, Central Java, Indonesia - darsono darsono; EDY RIWIDIHARSO; SLAMET SANTOSO; EMING SUDIANA; EDY yani; ERIE KOLLYA NASUTION; HEXA APRILLIANA; TITI CHASANAH (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Darsono, Riwidiharso E, Santoso S, Sudiana E, Yani E, Nasution EK, Aprilliana H, Chasanah T. 2020. Insect diversity in various distances to forest edge in small nature reserve: A case study of Bantarbolang Nature Reserve, Central Java, Indonesia. Biodiversitas 21: 4821-4828. A nature reserve is a conservation area with the objective of conserving the biodiversity of the flora and fauna within its boundaries. However, many nature reserves are fragmented into small extent and isolated from natural habitat, causing the so-called edge effect. This research aimed to investigate insect diversity across various distances to forest edge in small and isolated protected areas. Research was conducted in the Bantarbolang Nature Reserve, Pemalang District, Central Java, Indonesia. A survey was conducted to determine the diversity of insects, especially those from the Diptera (flies), Lepidoptera (butterfly), and Hymenoptera (bees and wasp) orders. The environmental parameters recorded were temperature, humidity, and flowering plant diversity and abundance. Line transects were laid at a length of 100 m, parallel to the forest edge at three different distance ranges from the edge: 0-50 m, 50-100 m, and 100-150 m. Species diversity was measured using the Shannon-Wiener index, evenness index, and Sorensen similarity index. Over the 4-month study period, 1713 individual insects from 63 species and from the following three orders were found: Lepidoptera (Rhopalocera; 33 species, 5 families, 932 individuals); Hymenoptera (20 species, 423 individuals) and Diptera (10 species, 7 families, 376 individuals). The highest diversity was found at the edge of the forest and the lowest at the distance of 100-150 m from the forest edge. While the study area can support a diversity of insects, especially pollinating insects, but it is unable to support the conservation of light-sensitive butterflies. The results of this study suggest that small nature reserve can support a diversity of pollinating insects, especially from the Diptera, Lepidoptera, and Hymenoptera. However, it has limited conservation potential because of the significant impact of forest edges on species composition, especially on specialist butterfly species with habitat in forest interior.